Indonesia Defense Alliance Probability in the Free-Active Foreign Policy - Amin Santoso, Tommi; Christine Sri Marnani, (Technium Social Sciences Journal, 2020)
Since its independence, Indonesia has chosen to be a neutral and impartial on the side of any force in its foreign policy, known as a Free-Active Foreign Policy. Likewise, in the military policy related to the alliance, explained in the White paper of Indonesia Defense Minister (2015), Indonesia will not join any military alliance. However, with the unprecedented Minimum Essential Force (MEF), which incompleted, the development of the area's strategic environment with the incoming varieties of potential threats, is there any possibility for Indonesia to conduct Alliance in order to improve its military capability? This paper focuses on the issue of problems regarding to the possibility of the Indonesian alliance in the present, with the status of free-active foreign politics. Data sources and data in this paper obtained from a variety of books and journals, supported by some information from the news media. The main purpose of the discussion in this paper is to find factors that allow Indonesia conducting an alliance in the future, with several sub discussions about the history of Indonesian cooperation shafts in the field of defense, cost and benefits in conducting Alliance, and challenges that Indonesia will encounter in case of joining an alliance.